Preparation method and application of cerium-based double-layer composite material coated with indium zinc sulfide
Through ultrasonic-assisted MOF ligand exchange technology, a cerium-based bilayer composite material coated with indium zinc sulfide is formed, which solves the problems of low carrier separation efficiency and structural stability of indium zinc sulfide in the field of photoelectro-catalytics, and achieves high efficiency, Stable catalytic hydrogen production effect.
Patent Information
- Application Number
- CN202411370724.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing indium zinc sulfide (ZnIn2S4) has low carrier separation efficiency and is susceptible to photocorrosion in the field of photoelectric catalysis, which limits its application in the field of catalytic hydrogen production. Moreover, the stability of the MOF frame structure is difficult to maintain during hydrothermal synthesis, and the yield is Lower.
Using ultrasonic-assisted MOF ligand exchange technology, the synthesis temperature and solution system are optimized by modifying Ce(IV)-MOF material with zinc salt and indium salt to form a cerium-based bilayer composite ZnIn2S4 coated with indium zinc sulfide. /MOF improves its reaction efficiency and stability of catalytic hydrogen production.
The catalytic hydrogen production efficiency and stability of ZnIn2S4 were significantly improved, the yield was increased to 82%, and the dispersion and catalytic reaction performance were significantly improved, with good application prospects.
Smart Images

Figure CN119265709A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of photoelectrocatalysis, and in particular to a preparation method and application of a cerium-based double-layer composite material coated with indium zinc sulfide. Background Art
[0002] The development of hydrogen production technology plays an important role in promoting energy transformation, responding to environmental challenges, and promoting economic development. Among them, photoelectrocatalytic water decomposition to produce hydrogen is considered to be one of the most promising new energy technologies. This technology uses solar energy as the main energy source and uses electrocatalysis to decompose water to produce hydrogen. It has the advantages of clean and environmental protection, energy saving and consumption reduction, and flexible energy storage. In 1972, Honda, Fujishima and others published a study in the journal Nature showing that titanium dioxide electrodes can decompose water to produce hydrogen under bias and light conditions. However, the quantum utilization efficiency of photoelectrocatalysis has always been very low, so that there has been no significant progress in research in this field. Therefore, the research and development of efficient and stable catalyst materials is one of the key topics in photoelectrocatalytic hydrogen production.
[0003] In recent years, ternary sulfide zinc indium sulfide (ZnIn2S4) has attracted more and more attention. This layered ternary metal sulfide has the characteristics of narrow band gap (2.06-2.85eV), non-toxicity, good visible light absorption, and its conduction band potential is very negative (up to -1.18V vs. SHE), with strong reduction ability, which is very suitable for photoelectrocatalytic hydrogen production. However, ZnIn2S4 has low carrier separation efficiency and is susceptible to photocorrosion, which seriously limits its application in the field of catalytic hydrogen production.
[0004] In order to improve the reaction efficiency and stability of catalytic hydrogen production of ZnIn2S4 materials, researchers have conducted many explorations, including element doping, defect engineering, heterostructure construction and co-catalyst loading methods, etc. Patent CN117258847A discloses a ZnIn2S4-MOF homojunction photocatalyst and its preparation method and application. The present invention further improves on this basis to obtain a cerium-based double-layer composite material coated with indium zinc sulfide with better photocatalytic performance. Summary of the invention
[0005] The present invention provides a preparation method and application of a cerium-based double-layer composite material coated with indium zinc sulfide, and utilizes ultrasound-assisted MOF ligand exchange technology to avoid the Ce(IV) reduction behavior during hydrothermal synthesis of functionalized Ce(IV)-MOF, and well maintains the MOF regular octahedral framework structure; ZnIn2S4 in-situ grows a composite ZnIn2S4 material, optimizes the composite synthesis temperature and solution system, obtains a ZnIn2S4 double-layer coating structure, and improves the yield and dispersibility of ZnIn2S4. The prepared ZnIn2S4 / MOF composite material has excellent reaction efficiency and stability for photoelectrocatalytic hydrogen production.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The method for preparing a cerium-based double-layer composite material coated with indium zinc sulfide comprises the following steps: ① The Ce(IV)-MOF material is dispersed in a solvent, an organic ligand containing hydroxyl groups is added, and an ultrasonic reaction is performed at room temperature to obtain a modified Ce(IV)-MOF material, which is recorded as Ce-UiO-(OH)2; the solvent is a mixed solvent of DMF and methanol; the ultrasonic frequency is 30-55kHz; ② Disperse the modified Ce(IV)-MOF material Ce-UiO-(OH)2 in a mixed solution of water and glycerol, add zinc salt and indium salt and stir, then add thioacetamide and stir, and heat to obtain the product, a cerium-based double-layer composite material coated with indium zinc sulfide, recorded as ZnIn2S4 / Ce-UiO-(OH)2, abbreviated as ZnIn2S4 / MOF.
[0007] Preferably, the preparation method of Ce(IV)-MOF material is as follows: dissolving terephthalic acid ligand in DMF, adding into cerium ammonium nitrate aqueous solution, mixing evenly; heating to react, and obtaining Ce(IV)-MOF material. Post-treatment of the reaction solution is as follows: cooling to room temperature, centrifuging to separate white solid, washing with DMF and acetone in turn, centrifuging to separate and dry, and obtaining Ce(IV)-MOF material.
[0008] As a further preference, the molar ratio of the terephthalic acid ligand to the ammonium cerium nitrate is (0.5-2):1; the heating reaction condition is stirring the reaction at 100-120° C. for 0.5-2 h.
[0009] Preferably, the Ce(IV)-MOF material is ultrasonically dispersed in the solvent.
[0010] Preferably, the solvent in step ① is a mixed solvent of DMF and methanol in a volume ratio of 1:(1-6).
[0011] Preferably, the hydroxyl-containing organic ligand in step ① is 2-hydroxyterephthalic acid or 2,5-dihydroxyterephthalic acid; the molar ratio of the organic ligand to MOF is (1-6):1, and more preferably 4:1.
[0012] Preferably, the ultrasonic reaction in step ① is a secondary ultrasonic reaction: the hydroxyl-containing organic ligand is divided into two parts, the Ce(IV)-MOF material is dispersed in a solvent, the first part of the hydroxyl-containing organic ligand is added, and the ultrasonic reaction is carried out at room temperature; the solid is separated from the reaction liquid, the second part of the hydroxyl-containing organic ligand is added, dispersed in a solvent, and the ultrasonic reaction is carried out at room temperature to obtain a modified Ce(IV)-MOF material Ce-UiO-(OH)2.
[0013] Preferably, the ultrasonic time in step ① is 5 min-2 h, more preferably 10 min. The ultrasonic power is 35-180 W.
[0014] Preferably, the post-treatment of the reaction solution in step ① is: centrifugal separation of the solid, washing with DMF and acetone in sequence, centrifugal separation and drying to obtain a modified Ce(IV)-MOF material Ce-UiO-(OH)2.
[0015] Preferably, in step ②, the volume ratio of water to glycerol is (2-3):1, and the water is deionized water.
[0016] Preferably, in step ②, the zinc salt is one of zinc chloride, zinc nitrate and zinc acetate; the indium salt is one of indium chloride, indium nitrate and indium acetate; and the molar ratio of zinc ion, indium ion and thioacetamide is 1:2:4.
[0017] Preferably, in step ②, zinc salt and indium salt are added and stirred for 30-60 min, then thioacetamide is added and stirred for 20-30 min, and the mixture is heated to 40-55° C. and stirred for 3-12 h to obtain the product.
[0018] Preferably, the molar ratio of indium zinc sulfide to MOF is (1-4):1, more preferably 3:1.
[0019] The present invention also provides the application of the cerium-based double-layer composite material coated with indium zinc sulfide prepared by the preparation method in photoelectrocatalytic hydrogen production. Compared with traditional indium zinc sulfide, the catalytic hydrogen production efficiency of the composite material is significantly improved, the catalytic reaction stability is significantly enhanced, and it has good application prospects.
[0020] Therefore, the beneficial effects of the present invention are: At present, ZnIn2S4 / MOF composite material technology still exists: (1) Problem 1: Modified Ce(IV)-MOF is difficult to synthesize because Ce(IV) has a low reduction potential and is easily reduced to Ce(III) in an environment where electron-donating functional groups are introduced, resulting in the collapse of the MOF framework structure. In response to the first problem, the present invention successfully prepared an electron-donating functional group-modified Ce(IV)-MOF with a high ligand exchange rate by selecting a suitable solvent and ultrasonic conditions. Compared with the traditional hydrothermal synthesis, the synthesis method is fast and simple and maintains the MOF framework structure well. The pKa of the organic ligand containing the functional group will affect the effectiveness of ultrasonic ligand exchange. Carboxylic acid ligands with higher pKa will lead to stronger coordination with Lewis acidic metal nodes. Since the pKa values of hydroxyl ligands are higher than the original pKa values of terephthalic acid, it shows that the hydroxyl ligands have stronger coordination with Lewis acidic metal nodes, so they can replace the terephthalic acid ligands with weak coordination ability under ultrasonic environment.
[0021] (2) Problem 2: The hydrothermal synthesis temperature of ZnIn2S4 is relatively high, and the stability of the MOF framework structure is difficult to maintain; the yield of ZnIn2S4 prepared at low temperature in the composite preparation is also relatively low.
[0022] In response to the second problem, the present invention optimizes the composite method. In the prior art, it is just a simple mixture of ZnIn2S4 and MOF. The present invention is a double-layer coating structure, and the synthesis temperature and solution system are optimized. The yield of sulfide coated by the low-temperature composite method is increased from 49% to 82%, and the dispersibility and yield of sulfide are further improved. Specifically, the modified Ce(IV)-MOF material Ce-UiO-(OH)2 is ultrasonically dispersed in a mixed solution of deionized water and glycerol at room temperature to obtain the core structure of the double-layer coating structure; then zinc salt and indium salt are added and stirred for a period of time, and the metal ions are first adsorbed on MOF to prepare for the subsequent in-situ growth; then a sulfur source is added and stirred for a period of time, and the sulfur source is precipitated and grown; finally, it is heated at a low temperature of 40-55°C to obtain a cerium-based double-layer composite material ZnIn2S4 / Ce-UiO-(OH)2 coated with indium zinc sulfide. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The X-ray diffraction patterns (XRD) of the products of Example 1, Examples 18-21, and Comparative Example 2 are shown.
[0024] Figure 2 This is the thermogravimetric analysis (TGA) curve of the product in Example 1.
[0025] Figure 3 The hydrogen nuclear magnetic resonance spectrum of the product of Example 1 is ( 1 1H NMR).
[0026] Figure 4 The nitrogen adsorption-desorption isotherms (BET) of the products of Example 1, Examples 18-21, and Comparative Example 2 are shown.
[0027] Figure 5 These are electron microscope images of the products of Example 1, Example 20, and Comparative Example 2.
[0028] Figure 6 This is the element scanning distribution diagram of the products of Example 1, Example 20, and Comparative Example 2.
[0029] Figure 7 This is a diagram of the photocatalytic hydrogen production efficiency of the products of Example 1, Examples 18-21, and Comparative Example 2.
[0030] Figure 8 This is a diagram of the catalytic hydrogen production efficiency of Example 20 and Comparative Example 3.
[0031] Fig. 9The photoelectrocatalytic hydrogen production voltammetric characteristic curves of the products of Example 1, Example 20, and Comparative Example 2.
[0032] Fig.10 This is the stability diagram of the cyclic catalytic hydrogen production of the products of Example 20 and Comparative Example 2.
[0033] Fig.11 This is the scanning electron microscope (SEM) image of Comparative Example 1.
[0034] Fig.12 This is the nitrogen adsorption-desorption isotherm (BET) of the product of Comparative Example 1.
[0035] Fig.13 This is the scanning electron microscope (SEM) image of Comparative Example 3. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is further described below through specific embodiments.
[0037] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art. Unless otherwise specified, parts are all weight parts, temperatures are expressed in ° C or at ambient temperature, and pressures are atmospheric pressure or near atmospheric pressure. There are many variations and combinations of reaction conditions (such as component concentrations, desired solvents, solvent mixtures, temperatures, pressures, and other reaction ranges) and conditions that can be used to optimize the purity and yield of the product obtained by the method, and only reasonable routine experiments will be required to optimize such method conditions.
[0038] 1. Preparation of modified Ce(IV)-MOF material Ce-UiO-(OH)2 (1) Preparation of Ce(IV)-MOF materials Weigh the terephthalic acid ligand at room temperature and dissolve it in N,N-dimethylformamide solvent by ultrasonication, then add it dropwise into the aqueous solution of cerium ammonium nitrate at room temperature, the molar ratio of terephthalic acid ligand to cerium ammonium nitrate is (0.5-2):1, and stir magnetically. Transfer the mixture to an oil bath at 100-120℃ and stir magnetically for 0.5-2h.
[0039] The reaction solution was cooled to room temperature, and the white solid was separated by centrifugation. The solid was washed with N,N-dimethylformamide and acetone in sequence, and then centrifuged and dried to obtain Ce(IV)-MOF material.
[0040] (2) Preparation of modified Ce(IV)-MOF material Ce-UiO-(OH)2 The Ce(IV)-MOF material is weighed at room temperature, ultrasonically dispersed in a solvent, and a hydroxyl-containing organic ligand (2-hydroxyterephthalic acid or 2,5-dihydroxyterephthalic acid) is added, the molar ratio of the organic ligand to the MOF is (1-6):1 (more preferably 4:1), and the ligand exchange reaction is performed by ultrasound at room temperature, and the reaction conditions are: ultrasonic frequency 30-55kHz, ultrasonic power 35-180W, and ultrasonic time 5min-2h (more preferably 10min). The hydroxyl-containing organic ligand can be 2-hydroxyterephthalic acid or 2,5-dihydroxyterephthalic acid; the solvent is a mixed solvent of DMF and methanol, more preferably a mixed solvent of DMF and methanol in a volume ratio of 1:(1-6).
[0041] Preferably, the ultrasonic reaction is a secondary ultrasonic reaction: the hydroxyl-containing organic ligand is divided into two parts, the Ce(IV)-MOF material is dispersed in a solvent, the first part of the hydroxyl-containing organic ligand is added, and the ultrasonic reaction is carried out at room temperature for 5min-2h; the solid is separated from the reaction liquid, the second part of the hydroxyl-containing organic ligand is added, dispersed in a solvent, and the ultrasonic reaction is carried out at room temperature for 5min-2h.
[0042] The reaction solution was centrifuged to separate the solid, which was washed with N,N-dimethylformamide and acetone in sequence, centrifuged and dried to obtain a modified Ce(IV)-MOF material, recorded as Ce-UiO-(OH)2.
[0043] Example 1 A method for preparing a modified Ce(IV)-MOF material Ce-UiO-(OH)2, comprising the following steps: (1) Preparation of Ce(IV)-MOF materials At room temperature, 498.0 mg of terephthalic acid was weighed and ultrasonically dissolved in 19.2 mL of N,N-dimethylformamide solvent to obtain material A1. At room temperature, 1644.0 mg of cerium ammonium nitrate Ce(NH4)2(NO3)6 was weighed and ultrasonically dissolved in 6.4 mL of deionized water to obtain material B1. Material A1 was added dropwise to material B1, and the mixed solution was transferred to a 100°C oil bath for hydrothermal reaction for 20 minutes.
[0044] After the reaction solution was cooled to room temperature, the precipitate was separated and collected by centrifugation at 8500 rpm for 6 min, washed three times with 15.0 mL of N,N-dimethylformamide and three times with 15.0 mL of acetone, and the white solid was separated by centrifugation at 8500 rpm for 6 min. The white solid was dried at 40°C in a vacuum overnight to obtain Ce(IV)-MOF material.
[0045] (2) Preparation of modified Ce(IV)-MOF material Ce-UiO-(OH)2 At room temperature, 65.2 mg of the Ce(IV)-MOF material prepared in Example 1 and 79.2 mg of 2,5-dihydroxyterephthalic acid were weighed and ultrasonically dispersed in a mixed solution of 5 mL of DMF and 20 mL of methanol. Ultrasonic exchange was performed at room temperature for 10 min, with an ultrasonic frequency of 40 kHz and an ultrasonic power of 100 W.
[0046] The solid was separated by centrifugation, and 79.2 mg of 2,5-dihydroxyterephthalic acid was added, and the solid was dispersed in a mixed solution of 5 mL of DMF and 20 mL of methanol for a second time. The solid was ultrasonically exchanged at room temperature for 10 min with an ultrasonic frequency of 40 kHz and an ultrasonic power of 100 W.
[0047] The precipitate was collected by centrifugation, washed three times with 10.0 mL N, N-dimethylformamide and 10.0 mL acetone, each time standing for 1 hour for exchange, and the solid was separated by centrifugation at 8500 rpm for 6 min. The solid was dried overnight at 40°C in a vacuum to obtain the product modified Ce(IV)-MOF material Ce-UiO-(OH)2, which is denoted as Ce-UiO-(OH)2 or MOF (Ce-UiO-(OH)2) (abbreviated as MOF) in the drawings of the specification.
[0048] Example 2 The difference from Example 1 is that a one-step ultrasonic method is used. The details are as follows: A method for preparing a modified Ce(IV)-MOF material Ce-UiO-(OH)2, comprising the following steps: (1) Preparation of Ce(IV)-MOF materials At room temperature, 498.0 mg of terephthalic acid was weighed and ultrasonically dissolved in 19.2 mL of N,N-dimethylformamide solvent to obtain material A1. At room temperature, 1644.0 mg of cerium ammonium nitrate Ce(NH4)2(NO3)6 was weighed and ultrasonically dissolved in 6.4 mL of deionized water to obtain material B1. Material A1 was added dropwise to material B1, and the mixed solution was transferred to a 100°C oil bath for hydrothermal reaction for 20 minutes.
[0049] After the reaction solution was cooled to room temperature, the precipitate was separated and collected by centrifugation at 8500 rpm for 6 min, washed three times with 15.0 mL of N,N-dimethylformamide and three times with 15.0 mL of acetone, and the white solid was separated by centrifugation at 8500 rpm for 6 min. The white solid was dried at 40°C in a vacuum overnight to obtain Ce(IV)-MOF material.
[0050] (2) Preparation of modified Ce(IV)-MOF material Ce-UiO-(OH)2 At room temperature, 65.2 mg of the Ce(IV)-MOF material prepared in Example 1 and 158.4 mg of 2,5-dihydroxyterephthalic acid were weighed and ultrasonically dispersed in a mixed solution of 5 mL of DMF and 20 mL of methanol. Ultrasonic exchange was performed at room temperature for 10 min, with an ultrasonic frequency of 40 kHz and an ultrasonic power of 100 W.
[0051] The precipitate was collected by centrifugation, washed three times with 10.0 mL N,N-dimethylformamide and 10.0 mL acetone, each time standing for 1 hour for exchange, and centrifuged at 8500 rpm for 6 min to separate the colored solid, which was dried overnight at 40°C in a vacuum to obtain the modified Ce(IV)-MOF material Ce-UiO-(OH)2.
[0052] Example 3-11 The difference from Example 2 is that the type of solvent used for the ultrasonic reaction in step (2) of Example 3-11 to prepare the modified Ce(IV)-MOF material Ce-UiO-(OH)2 is different, as shown in Table 1. The obtained Ce-UiO-(OH)2 was subjected to nuclear magnetic resonance hydrogen spectrum analysis to obtain the exchange rate of 2,5-dihydroxyterephthalic acid after exchange.
[0053] Table 1. Effect of ultrasonic solvent on ligand exchange rate Ultrasonic reaction solvent (25 mL) Ligand exchange rate % Example 2 DMF / methanol volume ratio 1:4 85 Example 3 Methanol 78 Example 4 Ethanol 67 Example 5 DMF 28 Example 6 DMF / Methanol volume ratio 1:1 80 Example 7 DMF / methanol volume ratio 1:3 82 Example 8 DMF / methanol volume ratio 1:5 83 Example 9 DMF / methanol volume ratio 1:6 83 Example 10 Ethanol / methanol volume ratio 1:1 72 Embodiment 11 Ethanol / methanol volume ratio 1:4 74 From Table 1, the polarity of solvents is different, methanol>DMF>ethanol. The greater the polarity, the more it can help polar organic ligand exchange. The exchange rate of DMF single solvent is low, because: DMF will dissolve organic ligands (but it is difficult to dissolve ligands in MOF that have been coordinated and fixed with the metal center), so the dissolution effect>ligand exchange, resulting in a low exchange rate. The effect of DMF / methanol mixed solvent is enhanced, because: the strong polar methanol solvent promotes ligand exchange, and a small amount of DMF helps ligand dissolution. There is a synergistic effect of ligand dissolution-ligand exchange between the two. Therefore, although the exchangeability of DMF alone is not high, it cooperates with methanol to form a synergistic effect of original ligand dissolution + new ligand exchange, which enhances the exchange rate. As the DMF content increases, ligand dissolution will dominate, resulting in a decrease in the exchange rate. Therefore, the ratio of the two must be within an appropriate range to achieve the best effect. Both methanol / ethanol mixed solvents are ligand exchange, and there is no synergistic effect, so the exchange rate is between the two single solvents, and no unexpected effect is produced.
[0054] Examples 12-14 The difference from Example 2 is that the ultrasonic frequencies in step (2) of Examples 12-14 are different when preparing the modified Ce(IV)-MOF material Ce-UiO-(OH)2, as shown in Table 2.
[0055] Table 2. Effect of ultrasound frequency on ligand exchange rate Ultrasonic frequency (kHz) Ligand exchange rate % Example 2 40 85 Example 12 28 71 Embodiment 13 50 80 Embodiment 14 60 73 From Table 2, ultrasound mainly provides energy for dissolving the solvent and exchanging ligands. As the energy increases, the ligand exchange law improves. However, too high energy will cause the MOF framework structure to collapse, so the ultrasound frequency needs to be within a reasonable range.
[0056] Examples 15-17 The difference from Example 2 is that the ultrasonic time is different when preparing the modified Ce(IV)-MOF material Ce-UiO-(OH)2 in step (2) of Examples 15-17, as shown in Table 3.
[0057] Table 3. Effect of ultrasound time on ligand exchange rate Ultrasonic time (min) Ligand exchange rate % Example 1 Repeat twice for 10 minutes 89 Example 2 10 85 Embodiment 15 2 71 Example 16 5 80 Embodiment 17 15 73 From Table 3, we can see that the ultrasonic time has an important influence on the ligand exchange rate. Ligand exchange requires a certain amount of energy and time. The exchange rate increases continuously when the ultrasonic time is 2min, 5min to 10min. Ultrasonication for 15 minutes, too much energy will further affect the original framework structure of MOF, causing slight damage to the structure and reducing the ligands in MOF. After 10 minutes, the MOF is placed in a new solution + ligand system for a second ultrasonic exchange step, which helps to further increase the exchange rate by 85% to 89%.
[0058] Comparative Example 1 The difference from Example 1 is that the modified Ce(IV)-MOF material Ce-UiO-(OH)2 is prepared by a traditional hydrothermal method. The details are as follows: A method for preparing a modified Ce(IV)-MOF material Ce-UiO-(OH)2, comprising the following steps: (1) 593.9 mg of 2,5-dihydroxyterephthalic acid was weighed and dissolved in 19.2 mL of N,N-dimethylformamide solvent by ultrasonication at room temperature to obtain material A8.
[0059] (2) At room temperature, 1644.0 mg of Ce(NH4)2(NO3)6 was weighed and dissolved in 6.4 mL of deionized water by ultrasonication to obtain material B8.
[0060] (3) Material A8 was added dropwise to material B8, and the mixed solution was transferred to a 100°C oil bath for hydrothermal reaction for 20 minutes. After cooling to room temperature, the precipitate was separated and collected by centrifugation at 8500 rpm for 6 minutes, and washed three times with 15.0 mL N, N-dimethylformamide and 15.0 mL acetone, and the white solid was separated by centrifugation at 8500 rpm for 6 minutes, and dried overnight at 40°C in vacuum to obtain the product, which was recorded as hydrothermal Ce-UiO-(OH)2 in the attached figure of the specification.
[0061] The SEM image of the hydrothermal Ce-UiO-(OH)2 product is as follows: Fig.11 As shown, the nitrogen adsorption and desorption isotherms are as follows Fig.12 As shown, it can be seen that the product preparation was unsuccessful.
[0062] 2. Preparation of Indium Zinc Sulfide Coated Cerium-Based Double-Layer Composite Material ZnIn2S4 / Ce-UiO-(OH)2 The modified Ce(IV)-MOF material Ce-UiO-(OH)2 is dispersed in a mixed solution of deionized water and glycerol in a volume ratio of (2-3):1, zinc salt and indium salt are added and stirred for 30-60 minutes, and then thioacetamide is added and stirred for 20-30 minutes, and heated to 40-55°C and stirred for 3-12 hours to obtain the product Indium Zinc Sulfide Coated Cerium-Based Double-Layer Composite Material. The zinc salt is one of zinc chloride, zinc nitrate, and zinc acetate; the indium salt is one of indium chloride, indium nitrate, and indium acetate; the molar ratio of zinc ion, indium ion, and thioacetamide is 1:2:4. The molar ratio of indium zinc sulfide to MOF is (1-4):1, and more preferably 3:1.
[0063] Embodiment 18 A method for preparing an indium zinc sulfide-coated cerium-based double-layer composite material, comprising the following steps: (1) At room temperature, 195.7 mg of the modified Ce(IV)-MOF material Ce-UiO-(OH)2 prepared in Example 2 was weighed and ultrasonically dispersed in a mixed solution of 6.0 mL of deionized water and 2.0 mL of glycerol. 43.4 mg of zinc acetate and 138.5 mg of indium chloride tetrahydrate were added, and magnetic stirring was performed for 30 minutes to obtain material A2.
[0064] (2) 142.0 mg of thioacetamide was weighed at room temperature and added to material A2. The mixture was magnetically stirred for 30 minutes to obtain material B2.
[0065] (3) Transfer material B2 to a 55°C water bath and stir and heat for 8 hours. After cooling to room temperature, centrifuge at 8000 rpm for 5 minutes to separate and collect the precipitate, wash it three times with 10.0 mL of deionized water and five times with 10.0 mL of anhydrous ethanol, centrifuge at 8000 rpm for 5 minutes to separate the white solid, and dry it overnight at 60°C under normal pressure to obtain a cerium-based double-layer composite material coated with indium zinc sulfide. Since the molar ratio of indium zinc sulfide to MOF (Ce-UiO-(OH)2) is 1:1, it is recorded as 1-ZnIn2S4 / MOF in the attached figure of the specification.
[0066] Embodiment 19 The difference from Example 18 is that the molar ratio of indium zinc sulfide to MOF (Ce-UiO-(OH)2) is 2:1. The details are as follows: A method for preparing an indium zinc sulfide-coated cerium-based double-layer composite material, comprising the following steps: (1) At room temperature, 50.0 mg of the modified Ce(IV)-MOF material Ce-UiO-(OH)2 prepared in Example 2 was weighed and ultrasonically dispersed in a mixed solution of 6.0 mL of deionized water and 2.0 mL of glycerol. 43.4 mg of zinc acetate and 138.5 mg of indium chloride tetrahydrate were added, and magnetic stirring was performed for 30 minutes to obtain material A3.
[0067] (2) 142.0 mg of thioacetamide was weighed at room temperature and added to material A3. The mixture was magnetically stirred for 30 minutes to obtain material B3.
[0068] (3) Transfer material B3 to a 55°C water bath and heat with stirring for 8 hours. After cooling to room temperature, centrifuge at 8000 rpm for 5 minutes to separate and collect the precipitate, wash it three times with 10.0 mL of deionized water and five times with 10.0 mL of anhydrous ethanol, centrifuge at 8000 rpm for 5 minutes to separate the white solid, and dry it overnight at 60°C under normal pressure to obtain a cerium-based double-layer composite material coated with indium zinc sulfide, which is marked as 2-ZnIn2S4 / MOF in the attached figure of the specification.
[0069] Embodiment 20 The difference from Example 19 is that the molar ratio of indium zinc sulfide to MOF (Ce-UiO-(OH)2) is 3:1. The details are as follows: A method for preparing an indium zinc sulfide-coated cerium-based double-layer composite material, comprising the following steps: (1) At room temperature, 50 mg of the modified Ce(IV)-MOF material Ce-UiO-(OH)2 prepared in Example 2 was weighed and ultrasonically dispersed in a mixed solution of 6.0 mL of deionized water and 2.0 mL of glycerol. 65.1 mg of zinc acetate and 207.8 mg of indium chloride tetrahydrate were added, and magnetic stirring was performed for 30 minutes to obtain material A4.
[0070] (2) Weigh 213.0 mg of thioacetamide at room temperature, add it to material A4, and stir magnetically for 30 minutes to obtain material B4.
[0071] (3) Transfer material B4 to a 55°C water bath and heat with stirring for 8 hours. After cooling to room temperature, centrifuge at 8000 rpm for 5 minutes to separate and collect the precipitate, wash it three times with 10.0 mL of deionized water and five times with 10.0 mL of anhydrous ethanol, centrifuge at 8000 rpm for 5 minutes to separate the white solid, and dry it overnight at 60°C under normal pressure to obtain a cerium-based double-layer composite material coated with indium zinc sulfide, which is marked as 3-ZnIn2S4 / MOF in the attached figure of the specification.
[0072] Embodiment 21 The difference from Example 20 is that the molar ratio of indium zinc sulfide to MOF (Ce-UiO-(OH)2) is 4:1. The details are as follows: A method for preparing an indium zinc sulfide-coated cerium-based double-layer composite material, comprising the following steps: (1) At room temperature, 50 mg of the modified Ce(IV)-MOF material Ce-UiO-(OH)2 prepared in Example 2 was weighed and ultrasonically dispersed in a mixed solution of 6.0 mL of deionized water and 2.0 mL of glycerol. 86.8 mg of zinc acetate and 277.0 mg of indium chloride tetrahydrate were added, and magnetic stirring was performed for 30 minutes to obtain material A5.
[0073] (2) Weigh 284.0 mg of thioacetamide at room temperature, add it to material A5, and stir magnetically for 30 minutes to obtain material B5.
[0074] (3) Transfer material B5 to a 55°C water bath and heat with stirring for 8 hours. After cooling to room temperature, centrifuge at 8000 rpm for 5 minutes to separate and collect the precipitate, wash three times with 10.0 mL of deionized water and five times with 10.0 mL of anhydrous ethanol, centrifuge at 8000 rpm for 5 minutes to separate the white solid, and dry overnight at 60°C at normal pressure to obtain a cerium-based double-layer composite material coated with indium zinc sulfide, which is marked as 4-ZnIn2S4 / MOF in the attached figure of the specification.
[0075] Examples 22-26 The difference from Example 18 is that the heating time in step (3) is different. As shown in Table 4, the actual content of ZIS is obtained by calculating the yield of indium zinc sulfide through ICP measurement.
[0076] Table 4. Effect of hydrothermal time on the yield of in situ grown indium zinc sulfide Ultrasonic time (h) In situ growth of indium zinc sulfide yield% Embodiment 18 8 82 Embodiment 22 2 28 Embodiment 23 4 53 Embodiment 24 6 69 Embodiment 25 10 82 Embodiment 26 12 82 Comparative Example 2 A method for preparing indium zinc sulfide, comprising the following steps: (1) At room temperature, 43.4 mg of zinc acetate and 138.5 mg of indium chloride tetrahydrate were weighed, ultrasonically dispersed in a mixed solution of 6.0 mL of deionized water and 2.0 mL of glycerol, and magnetically stirred for 30 minutes to obtain material A6.
[0077] (2) 142.0 mg of thioacetamide was weighed at room temperature and added to material A6. The mixture was magnetically stirred for 30 minutes to obtain material B6.
[0078] (3) Transfer material B6 to a 55°C water bath and heat with stirring for 8 hours. After cooling to room temperature, centrifuge at 8000 rpm for 5 minutes to separate and collect the precipitate, wash it three times with 10.0 mL of deionized water and five times with 10.0 mL of anhydrous ethanol, centrifuge at 8000 rpm for 5 minutes to separate the white solid, and dry it overnight at 60°C under normal pressure to obtain indium zinc sulfide, which is denoted as ZnIn2S4 in the attached figure of the specification.
[0079] Comparative Example 3 The difference from Example 20 is that the cerium-based double-layer composite material coated with indium zinc sulfide is prepared by a one-pot method. The details are as follows: A method for preparing an indium zinc sulfide-coated cerium-based double-layer composite material, comprising the following steps: At room temperature, weigh 50.0 mg of the modified Ce(IV)-MOF material Ce-UiO-(OH)2 obtained in Example 2 and ultrasonically disperse it in a mixed solution of 8.0 mL of deionized water and 2.0 mL of glycerol. Add 65.1 mg of zinc acetate, 207.8 mg of indium chloride tetrahydrate and 213.0 mg of thioacetamide and stir to fully dissolve them. Transfer to a 55°C water bath and stir and heat for 8 hours. After cooling to room temperature, centrifuge at 8000 rpm for 5 minutes to separate and collect the precipitate, wash three times with 10.0 mL of deionized water, wash five times with 10.0 mL of anhydrous ethanol, centrifuge at 8000 rpm for 5 minutes to separate the white solid, and dry it overnight at 60°C at normal pressure to obtain the product, which is recorded as one-pot method-ZnIn2S4 / Ce-UiO-(OH)2 in the attached figure of the specification.
[0080] Product appearance Fig.13 As shown, without the double-layer coating structure of the present invention, the yield of in-situ grown indium zinc sulfide is only 49%.
[0081] Performance Testing The product performance of each embodiment and comparative example was tested: (1) X-ray diffraction experiment was performed on the product. The results are as follows Figure 1 As shown. The modified Ce(IV)-MOF material Ce-UiO-(OH)2 obtained in Example 1 has similar standard diffraction patterns to Ce-UiO-66, indicating that the ultrasonic-assisted method has no effect on the MOF structure. The X-ray diffraction pattern of ZnIn2S4 obtained in Comparative Example 2 matches the hexagonal ZnIn2S4 standard diffraction card (PDF 65-2923). The cerium-based double-layer composite material ZnIn2S4 / MOF coated with indium zinc sulfide obtained in Examples 18-21 exhibits diffraction peaks similar to those of the MOF obtained in Example 1 and the ZnIn2S4 obtained in Comparative Example 2, indicating that when ZnIn2S4 is deposited on MOF, the MOF crystal structure remains stable. As the loaded ZnIn2S4 increases, the peak intensity attributable to ZnIn2S4 gradually increases, and the peak intensity attributable to MOF gradually weakens.
[0082] (2) The thermal stability analysis of Ce-UiO-(OH)2 obtained in Example 1 was performed. The results are as follows Figure 2As shown. MOF was heated from 30°C to 600°C in air at a rate of 10°C / min. The sample was kept at 600°C for 120 minutes and then cooled back to 30°C at a rate of -20°C / min. When the temperature exceeded 80°C, the MOF framework structure was slightly affected. At 80-250°C, the framework structure was basically stable. After 250°C, the framework structure collapsed rapidly.
[0083] (3) The Ce-UiO-(OH)2 obtained in Example 1 was subjected to nuclear magnetic resonance hydrogen spectrum analysis. The results are as follows Figure 3 As shown in Figure 2, 2,5-dihydroxyterephthalic acid ligands were successfully exchanged onto Ce-UiO by ultrasonic exchange, and the exchange rate after two exchanges was about 89%.
[0084] (4) A nitrogen adsorption and desorption experiment was carried out using the single MOF material obtained in Example 1, the single ZnIn2S4 material obtained in Comparative Example 2, and the composite materials obtained in Examples 18-21. The results are as follows: Figure 4 As shown. The prepared MOF and ZnIn2S4 have type I and type IV adsorption-desorption isotherms, respectively, indicating that they are microporous and mesoporous materials, respectively. All isotherms of the prepared ZnIn2S4 / MOF composite materials are type IV isotherms, and the starting point of their hysteresis loops is close to that of single ZnIn2S4, indicating that ZnIn2S4 covers the outer surface of MOF, blocks the micropores of MOF, and constructs a mesoporous structure similar to ZnIn2S4.
[0085] (5) The single MOF material obtained in Example 1, the single ZnIn2S4 material obtained in Comparative Example 2, and the 3-ZnIn2S4 / MOF composite material obtained in Example 4 were subjected to electron microscopy and element scanning analysis. The results are as follows: Figure 5 and 6 As shown. The prepared MOF exhibits a uniform octahedral structure, a smooth surface, and a particle size of about 200 nanometers. Single ZnIn2S4 materials are aggregated together to form flower-like microspheres. The Ce-MOF octahedral structure is determined by tetravalent Ce and coordinated chain organic matter, so the difficulty in introducing -(OH) series ligands is that -(OH)2 is an electron-donating group, which causes tetravalent Ce to be oxidized to trivalent Ce, resulting in structural collapse. Therefore, the traditional hydrothermal method cannot be used, and the present invention requires two steps: forming the MOF matrix octahedral structure, and then ultrasonically replacing the ligands therein. Figure 6 It shows that the ZnIn2S4 / MOF composite material is in the shape of nanospheres, but its surface has a furry flaky coating structure. Element scanning analysis shows that all elements (cerium, zinc, indium and sulfur) on the composite material are evenly distributed.
[0086] (6) Weigh 25.0 mg of each product of Example 1, Examples 18-21 and Comparative Example 2, and ultrasonically disperse them in 50 mL of Na2S / Na2SO3 aqueous solution. Under nitrogen atmosphere, visible light catalytic water hydrogen production test was carried out under 420 nm monochromatic LED light irradiation to investigate the effect of the introduced MOF ratio. The results are as follows: Figure 7 As shown in the figure, the efficiency of hydrogen production by the composite catalysts was significantly improved. With the increase of the content of introduced MOF, the hydrogen production activity first increased and then decreased. When the ratio of indium zinc sulfide to introduced MOF was 3.0, the efficiency of hydrogen production by the composite catalyst was the highest.
[0087] (7) Weigh 25.0 mg of each product of Example 20 and Comparative Example 3, and conduct visible light photocatalytic water hydrogen production test in 50 mL Na2S / Na2SO3 aqueous solution to investigate the effect of the double-layer coating structure on the catalytic hydrogen production activity of the composite. The results are as follows: Figure 8 Compared with traditional composite materials, the hydrogen production activity of double-layer coated composite materials with better dispersion is significantly improved.
[0088] (8) The single MOF material obtained in Example 1, the single ZnIn2S4 material obtained in Comparative Example 2, and the 3-ZnIn2S4 / MOF composite material obtained in Example 20 were drop-coated on FTO conductive glass to prepare a working electrode (1×2 cm). A platinum mesh was used as the counter electrode, a saturated Ag / AgCl electrode was used as the reference electrode, and an FX-300HU xenon lamp with a 420nm filter was used as the light source to measure the photoelectrocatalytic reaction efficiency of the catalyst in a sodium perchlorate electrolyte. Fig. 9 As shown, at a given potential, the electrode current density of proton reduction is 3-ZnIn2S4 / MOF>ZnIn2S4>MOF, and the proton reduction potential of the composite material is significantly reduced, indicating that the composite material is beneficial to improving the catalytic hydrogen production efficiency.
[0089] (9) Weigh 25.0 mg of each product of Example 20 and Comparative Example 2, and conduct 4 cycles of 8 hours of catalytic hydrogen production in a nitrogen atmosphere to investigate the stability of the ZnIn2S4 / MOF composite catalyst during the catalytic process. Fig.10 As shown in the figure, after four cycles, the hydrogen production activity of single ZnIn2S4 decreased by 51%, while the activity of the composite catalyst did not decrease significantly, indicating that the cyclic stability of the composite catalyst was significantly improved during the catalytic process.
[0090] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a cerium-based double-layer composite material coated with indium zinc sulfide, characterized in that: The following steps are involved: ① Disperse the Ce(IV)-MOF material in a solvent, add a hydroxyl-containing organic ligand, and perform an ultrasonic reaction at room temperature to obtain a modified Ce(IV)-MOF material Ce-UiO-(OH)2; the solvent is a mixed solvent of DMF and methanol; the ultrasonic frequency is 30-55 kHz; ② The modified Ce(IV)-MOF material is dispersed in a mixed solution of water and glycerol, zinc salt and indium salt are added and stirred, and then thioacetamide is added and stirred, and heating is performed to obtain the product, indium zinc sulfide-coated cerium-based double-layer composite material ZnIn2S4 / Ce-UiO-(OH)2.
2. The method for preparing the cerium-based double-layer composite material coated with indium zinc sulfide according to claim 1, characterized in that: The preparation method of Ce(IV)-MOF material is as follows: terephthalic acid ligand is dissolved in DMF, added into cerium ammonium nitrate aqueous solution, and mixed evenly; heating reaction is performed to obtain Ce(IV)-MOF material.
3. The method for preparing the cerium-based double-layer composite material coated with indium zinc sulfide according to claim 2, characterized in that: The molar ratio of the terephthalic acid ligand to the ammonium cerium nitrate is (0.5-2):1; the heating reaction conditions are stirring the reaction at 100-120°C for 0.5-2 h.
4. The method for preparing the cerium-based double-layer composite material coated with indium zinc sulfide according to claim 1, characterized in that: The solvent of step ① is a mixed solvent of DMF and methanol in a volume ratio of 1:(1-6).
5. The method for preparing the cerium-based double-layer composite material coated with indium zinc sulfide according to claim 1, characterized in that: Step ① The hydroxyl-containing organic ligand is 2-hydroxyterephthalic acid or 2,5-dihydroxyterephthalic acid; the molar ratio of the organic ligand to MOF is (1-6):
1.
6. The method for preparing the cerium-based double-layer composite material coated with indium zinc sulfide according to claim 1, characterized in that: The ultrasonic reaction of step ① is a secondary ultrasonic reaction: the hydroxyl-containing organic ligand is divided into two parts, the Ce(IV)-MOF material is dispersed in a solvent, the first part of the hydroxyl-containing organic ligand is added, and the ultrasonic reaction is carried out at room temperature; the solid is separated from the reaction liquid, the second part of the hydroxyl-containing organic ligand is added, dispersed in a solvent, and the ultrasonic reaction is carried out at room temperature to obtain a modified Ce(IV)-MOF material.
7. The method for preparing the cerium-based double-layer composite material coated with indium zinc sulfide according to claim 1 or 6, characterized in that: The ultrasonic time in step ① is 5min-2h.
8. The method for preparing the cerium-based double-layer composite material coated with indium zinc sulfide according to claim 1, characterized in that: In step ②, the volume ratio of water to glycerol is (2-3):1; the molar ratio of indium zinc sulfide to MOF is (1-4):
1.
9. The method for preparing the cerium-based double-layer composite material coated with indium zinc sulfide according to claim 1 or 8, characterized in that: In step ②, the zinc salt is one of zinc chloride, zinc nitrate and zinc acetate; the indium salt is one of indium chloride, indium nitrate and indium acetate.
10. Use of the cerium-based double-layer composite material coated with indium zinc sulfide obtained by the preparation method according to any one of claims 1 to 9 in photoelectrocatalytic hydrogen production.
Citation Information
Patent Citations
Preparation method of cerium-doped NH2-UiO-66 / indium zinc sulfide composite visible-light-induced photocatalysts
CN110124740A
2D / 2D indium zinc sulfide / MXene photocatalytic heterojunction hydrogen production material and preparation method thereof
CN112827503A
Preparation method and application of cerium-doped NH2-UiO-66 / cadmium indium sulfide composite photocatalyst for CO2 reduction
CN116532161A
Preparation and application of MOF derivative organic photoelectrochemical transistor sensor
CN116660354A
ZnIn2S4-MOF homojunction photocatalyst as well as preparation method and application thereof
CN117258847A
Cited By
Preparation method and application of amide plasmalogen compound
CN119876292A
Preparation method and application of cerium-based metal organic framework photoelectric catalyst
CN120060900A